A comprehensive exergoeconomic analysis of absorption power and cooling cogeneration cycles based on Kalina, part 1: Simulation. (15th February 2018) - Shokati, Naser; Ranjbar, Faramarz; Yari, Mortaza
Highlights: Exergoeconomic simulation of absorption power/cooling cycles based on Kalina. Calculation of the cost rate of all streams in the considered cogeneration cycles. Determining the values of important exergoeconomic parameters of the cycles. The contribution of various components in values of C ̇ D, tot + Z ̇ tot and E ̇ x D, tot . Specifying the critical components of the cycles from exergoeconomic viewpoint. Abstract: In this study, ammonia-water double effect absorption refrigeration/Kalina cogeneration cycle and two different configurations of ammonia-water absorption refrigeration/Kalina cogeneration cycles are considered for heat recovery from the high temperature heat source. In this type of cogeneration cycles, power generation and refrigeration cycles have become a single cycle that power and cooling are produced simultaneously in a common loop. After applying the first and second laws of thermodynamics on the components of the considered cycles and the validation of them, by developing SPECO approach on the considered cogeneration cycles, the cycles are simulated from the exergoeconomic viewpoint. For this purpose, the unit cost and cost rate of all streams of the cycles as well as the important thermodynamic and thermoeconomic parameters of each component and the considered cogeneration cycles are calculated. The simulation results indicate that although the thermodynamic efficiency of the double effect absorption refrigeration/Kalina cogeneration cycle is much higher than thermodynamic efficiency of other considered cycles, the economic performance of this cycle is not very desirable. Among the considered cogeneration cycles, the best thermoeconomic performance belongs to the first configuration absorption refrigeration/Kalina cycle. Also, in all cases, the boiler and the low pressure absorber have the highest sum of exergy destruction and capital investment cost rates and should be taken into consideration from exergoeconomic viewpoint for better performance of the cogeneration cycles. The most critical components from the exergy viewpoint are also included boiler, the low pressure absorber and rectifier.